Solving systems of nonhomogeneous coupled linear matrix differential equations in terms of Mittag-Leffler matrix functions - Kongyaksee, Rungpailin; Chansangiam, Pattrawut (My University, 2019)
In this paper, we investigate systems of nonhomogeneous coupled linear matrix differential equations. Applying Kronecker products, the vector operator, and matrix convolution product, we obtain explicit formula of the general solution to this system in terms of matrix series concerning exponentials and Mittag-Leffler functions.
Keywords: Kronecker product; Linear matrix differential equation; Matrix convolution product; Mittag-Leffler function; Vector operator